Climate-related disclosure commitment of the lenders, credit rationing, and borrower environmental performance - Hasan, Iftekhar; Lee, Haekwon; Qiu, Buhui; Saunders, Anthony (Review of Accounting Studies, 2026)
U sing lenders who become members of the Task Force on Climate-Related Financial Disclosures (TCFD) as an exogenous shock, we examine whether and how lenders’ commitment to transparent climate-related disclosures affects borrowers’ environmental performance. We find that borrowers of TCFD-member lenders, relative to control firms, significantly improve their environmental performance after the TCFD launch. Lenders’ disclosure commitments influence borrowers through credit rationing and monitoring. Specifically, polluting borrowers face higher borrowing costs, reduced access to credit, and greater incorporation of environmental action covenants in loan agreements. Additionally, polluting borrowers of TCFD-member lenders experience heightened financial constraints. Finally, borrowers of TCFD-member lenders are more likely to adopt the TCFD framework for climate-related disclosure after the TCFD establishment. Together, these findings illuminate the role of lenders in driving corporate environmental performance improvement through their commitment to transparent climate-related disclosures.